2003
DOI: 10.1128/jcm.41.8.3806-3815.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Sporadic Isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) in Hospitals and Their Similarities to Isolates of Community-Acquired MRSA

Abstract: Forty-one methicillin-resistant Staphylococcus aureus (MRSA) hospital isolates that clearly differed from the six major pandemic clones of MRSA in pulsed-field gel electrophoresis type, mecA and Tn554 polymorphism, and epidemic behavior were selected from an international strain collection for more detailed characterization. SpaA typing, multilocus sequence typing, and SCCmec (staphylococcal cassette chromosome mec) typing demonstrated extensive diversity among these sporadic isolates both in genetic backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
72
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 28 publications
9
72
1
2
Order By: Relevance
“…The presence of more than one different type of SCCmec in the same ST indicates, in congruence with other studies (1,7), that the MRSA clones arose at several occasions in the same genetic background by independent acquisition of SCCmec into methicillin-sensitive strains. This circumstance denotes the importance of combining MLST data with the SCCmec typing results when trying to understand the origins of MRSA.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of more than one different type of SCCmec in the same ST indicates, in congruence with other studies (1,7), that the MRSA clones arose at several occasions in the same genetic background by independent acquisition of SCCmec into methicillin-sensitive strains. This circumstance denotes the importance of combining MLST data with the SCCmec typing results when trying to understand the origins of MRSA.…”
Section: Discussionsupporting
confidence: 71%
“…MLST of large numbers of MRSA from different geographic areas has revealed that there are five major clonal lineages that are internationally dominating (1,4,24). However, community-acquired MRSA are found to possess more diverse evolutional origins compared to nosocomial strains (7,11,20,23,24), and they are predominantly carrying type IV SCCmec.…”
mentioning
confidence: 99%
“…Recently, methicillin-resistant Staphylococcus aureus (MRSA), methicillin-resistant Staphylococcus epidermidis, vancomycinresistant enterococci (VRE), and ampicillin-resistant Escherichia coli have emerged as common nosocomial (hospitalacquired) infections (2)(3)(4). The escalating resistance to conventional agents has inspired a substantial research effort directed toward investigating the potential of antimicrobial peptides (AMPs).…”
mentioning
confidence: 99%
“…Methicillin-resistant S. aureus (MRSA) strains of CC97 have been isolated from swine samples and so on. Many of these strains have been classified as SCCmec type IV, which appears to cause higher mobility than other SCCmec types [1]. Invasion and spread of SCCmec type IV strains in dairy barns may promote appearance of new MRSA strains adapted to cows.…”
mentioning
confidence: 99%